Distribution of total heterotrophic bacteria (THB) and Vibrio parahaemolyticus in shrimp culture ecosystem - Dalmin, G; Purushothaman, A; Kathiresan, K (Indian Journal of Fisheries, 2011)
The populations of total heterotrophic bacteria (THB) and Vibrio parahaemolyticus were analysed in modified extensive shrimp (Penaeus monodon) culture pond, located on the bank of Vellar estuary, Parangipettai, India, for ten months covering two consecutive culture operations. The microbial load in water, sediment and culture species was more in the first culture than the second. The microbial load increased with the days of culture, mainly due to the organic load in the pond environment, however, physico-chemical parameters such as salinity, temperature, pH and dissolved oxygen were within the permissible limits throughout the culture. Sediments had more bacterial load than water and shrimps. A heavy load of THB (40% vibrios) and V. parahaemolyticus was observed in the first culture that faced a serious viral disease problem (white spot disease) and mass mortality at the final stages of culture. The bacteria might have acted as primary pathogen by facilitating the entry of viron particles as well as secondary pathogen, leading to mass mortality of shrimps. Prophylactic measures, regular use of disinfectants and proper pond bottom management have reduced bacterial load in second disease-free successful culture operation.